Ectopic over-expression of miR-429 induces mesenchymal-to-epithelial transition (MET) and increased drug sensitivity in metastasizing ovarian cancer cells - Wang, Lijuan; Mezencev, Roman; Švajdler, Marián; Benigno, Benedict B; McDonald, John F (Gynecologic oncology, 2014)
OBJECTIVE: We recently determined that the ectopic over-expression of miR-429 and other members of the miR-200 family of microRNAs in ovarian cancer (OC) mesenchymal-like cell lines induces mesenchymal-to-epithelial transition (MET) with a concomitant increase in sensitivity to platinum drugs. We sought to determine if metastasizing OC cells isolated from an OC patient could also be induced by miR-429 to undergo MET and become sensitized to established first-line platinum-based therapies. METHODS: We established and characterized a new primary cell line (OCI-984) from free-floating OC cells isolated from the ascites fluid of an advanced stage OC patient. miR-429 was ectopically over-expressed in these cells. RESULTS: The over-expression of miR-429 in OCI-984 cells induced morphological, functional and molecular changes consistent with MET and a concomitant significant increase in the sensitivity of the converted cells to cisplatin. CONCLUSIONS: Our findings indicate that the miR-200 family of microRNAs, and miR-429 in particular, play a critical role in the functioning of OC metastasizing cells and that targeted delivery of miR-429, and perhaps other miR-200 family members, in combination with platinum-based chemotherapies may be an effective strategy in reducing OC metastasis and tumor recurrence.
Keywords: cisplatina; protinádorové látky; ženské pohlaví; Cisplatin; lidé; myši; myši nahé; epitelo-mezenchymální tranzice; senioři; Mice; MicroRNAs; Xenograft Model Antitumor Assays; Aged; xenogenní modely - testy protinádorové aktivity; Ovarian Neoplasms; Drug Screening Assays, Antitumor; Animals; Humans; nádorové buněčné linie; mikro RNA; Epithelial-Mesenchymal Transition; zvířata; Mice, Nude; Antineoplastic Agents; screeningové testy protinádorových léčiv; nádory vaječníků; Cell Line, Tumor; Female